The Development of Telegraphy, 1870–1900: A European Perspective on a World History Challenge - Wenzlhuemer, Roland (History compass, 2007)
This article puts forward that the study of so-called information societies and of the interplay of information technology and society in general needs to be amended from a historical perspective. Only by looking back further than the 1960s can the concept of an information revolution be critically evaluated. I argue that the study of information societies must at least go back until the invention and spread of electric telegraphy which has brought about the detachment of telecommunication from transport and thus created a virtual space of information. The essay seeks to provide some initial empirical findings in order to facilitate the identification of regional case studies with different degrees of global connectivity. Statistical data from the ITU archives in Geneva has been collected and indexed in order to illustrate how different regions in Europe and the wider world developed in telegraphic terms between 1870 and 1900. It is hoped and anticipated that these initial findings will be refined and shall eventually provide the structural basis for detailed historical comparisons between regions with different points of connection.